2021
DOI: 10.3389/frans.2021.709589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biological Age Prediction Models Using Clinical Biomarkers Commonly Measured in Clinical Practice Settings: AI Techniques Vs. Traditional Statistical Methods

Abstract: In this work, we used the health check-up data of more than 111,000 subjects for analysis, using only the data with all 35 variables entered. For the prediction of biological age, traditional statistical methods and four AI techniques (RF, XGB, SVR, and DNN), which are widely used recently, were simultaneously used to compare the predictive power. This study showed that AI models produced about 1.6 times stronger linear relationship on average than statistical models. In addition, the regression analysis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Our work considered machine learning methods (Multiple Linear Regression (MLR), Generalized Additive Models (GAM), Support Vector Machine (SVM), Adaboost, Gradient Boosting Decision Tree (GBDT), Light Gradient Boosting Machine (LGBM), Catboost, Xgboost, Extra Trees) and neural network methods (Deep Neural Networks (DNN), Convolutional Neural Network (CNN)) that can be used for regression analysis. The Pearson correlations, MAE, and RMSE between BA and CA are the indicators used to compare different BA estimation algorithms, which are done in the test set [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work considered machine learning methods (Multiple Linear Regression (MLR), Generalized Additive Models (GAM), Support Vector Machine (SVM), Adaboost, Gradient Boosting Decision Tree (GBDT), Light Gradient Boosting Machine (LGBM), Catboost, Xgboost, Extra Trees) and neural network methods (Deep Neural Networks (DNN), Convolutional Neural Network (CNN)) that can be used for regression analysis. The Pearson correlations, MAE, and RMSE between BA and CA are the indicators used to compare different BA estimation algorithms, which are done in the test set [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Pearson correlations, MAE, and RMSE between BA and CA are the preferred and most commonly used indicators to compare different BA estimation algorithms [ 25 , 26 ]. Exploring the associations of ML-BA with epidemiological variables (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Negative values of Δage (i.e., where BA is less than CA) are associated with the deceleration of aging and a lower risk of morbidity, hospitalization, and mortality [ 15 , 16 ]. One of the most innovative ways to estimate biological aging is by applying deep neural networks to circulating biomarkers [ 16 , 17 , 18 , 19 ]. Indeed, although this represents only a generic marker of biological aging and other markers or scales such as frailty and cognitive performance may better tag organ-specific aging [ 20 ] or the intrinsic aging capacity [ 21 , 22 ], blood-based estimates of BA can provide information on several aging domains within the human body because it can be based on a range of different circulating biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although this represents only a generic marker of biological aging and other markers or scales such as frailty and cognitive performance may better tag organ-specific aging [ 20 ] or the intrinsic aging capacity [ 21 , 22 ], blood-based estimates of BA can provide information on several aging domains within the human body because it can be based on a range of different circulating biomarkers. Indeed, previous studies identified prominent roles of glucose homeostasis, liver and kidney functionality, and inflammation, among other biomarkers [ 16 , 17 , 18 , 19 ]. Moreover, the wide availability of routine blood tests resulting from common clinical practice makes this a cost-effective estimator of biological aging, which could be used as a public health and healthy aging screening tool in the general population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Pearson correlations, MAE, and RMSE between BA and CA are the preferred and most commonly used indicators to compare different BA estimation algorithms, which are usually done in the test set [27,28]. In addition, exploring the associations of ML-BA with epidemiological variables (e.g.…”
Section: Introductionmentioning
confidence: 99%